Emotional skills and school success: An exploratory study of a programme of systemic intervention - Cardoso, Ana Paula (2019)
This paper presents a research aimed at understanding the contribution of an integrated and systemic intervention programme called Develop+ targeted at the development of appropriate social and emotional skills in students with disruptive behaviours, as well as their parents and teachers. The exploratory study was developed using an action-research methodology. The intervention was conducted over six months and included a baseline pre-test with a set of instruments and a post-test. The convenience sample involved six students from two 7th year classes of a school in the central region of Portugal, five parents and ten teachers. After the intervention, five students perceived very significant changes in their behaviours and only one didn’t feel any change in the way she has been behaving. Parents and teachers revealed a rather favourable perception regarding their participation in the programme, considering that it helped them to perceive some behaviours and practices less adjusted to their educational action. The results highlight the importance of a systemic intervention programme applied to students who display disruptive behaviours. The programme revealed an improvement of personal and social skills associated with a higher academic achievement. Also, the results demonstrated that parents and teachers’ emotional competences and well-being are quite important in developing and maintaining positive relationships with students required for their adaptation to school.